Sustainability and Strategy of Vegetable Crops Enterprises Based on Integrated Pest Management (Case Study in Mekarsaluyu Village, Cimenyan Subdistrict, Bandung Regency) - Anjelina, Patimah; Permana, Agus Dana; Alfianny, Rika (Jurnal Perlindungan Tanaman Indonesia, 2023)
Crop enterprises in Mekarsaluyu Village, Cimenyan Subdistrict, Bandung Regency have contributed to the economic activities of the local community. However, current vegetable crop enterprises are not suitable for the sustainable agriculture concept and face several obstacles in its sustainability, such as the availability of water, access to capital, farmers’ concern for environmental sustainability, as well as the role of farmer groups and farmer group association. Integrated pest management (IPM) is a sustainable agricultural production subsystem that can help control pests on vegetable crops, with the use of pesticides as a last resort. This study aims to assess the sustainability status and formulate a farming management strategy based on IPM. The sustainability status was analyzed using the uses the RAP-IPM (Rapid Appraisal for Integrated Pest Management) method which is a modification of the RAPFISH (Rapid Appraisal for Fisheries), and strategy was analyzed using the SWOT and the QSPM method. Respondents were determined by purposive sampling. The sustainability status of vegetable farming based on IPM tends to be quite sustainable with a sustainability index value of 58.23% and the prioritized management strategies are (1) strengthening farmer institutions including farmer groups and farmer groups associations, marketing institutions, and business groups agriculture in meeting the need for vegetable demand in the market; (2) development of environmentally friendly integrated pest control based control technology and preparation of effective and efficient alternative production facilities including land management, labor requirements, planting area in accordance with factual conditions in the field; and (3) strengthening agricultural financing institutions to meet the needs of agricultural production facilities and infrastructure.